The Impact of Diagnostic Stewardship on Clostridium difficile Infections. (4th October 2017) - Bischoff, Werner; Bubnov, Andrey; Palavecino, Elizabeth; Beardsley, James; Williamson, John; Johnson, James; Luther, Vera; Ohl, Christopher; El Helou, Guy; Huang, Glen; Stehle, John; Sanders, John
Abstract: Background: Clostridium difficile infections (CDI) pose a growing threat to hospitalized patients. This study assesses the impact of changing from a nucleic acid amplification test (NAAT) to a stepwise testing algorithm (STA) by using an enzyme immunoassay (GDH and toxin A/B) and confirmatory NAAT confirmation in specific cases. Methods: In an 885 bed academic medical center a 24 month pre-/post design was used to assess the effect of the STA for the following parameters: rates of enterocolitis due to C.diff (CDE), NHSN C.diff LabID events, CDI complications, mortality, antimicrobial prescription patterns, cluster occurrences; and testing, treatment, and isolation costs. Inpatient data were extracted from ICD-9/10 diagnosis codes, infection prevention, and laboratory databases. Results: The STA significantly decreased the number of CDE ICD9/10 codes, HO, CO, and CO-HCFA C.diff LabID event rates by 65%, 78%, 75%, and 75%, respectively. Similar reductions were noted for associated complications such as NHSN defined colon surgeries (-61%), megacolon (-64%), and acute kidney failure (-55%). CDE unrelated complication rates for colon surgeries and acute kidney failure remained constant while the diagnosis of megacolon decreased but not significantly (-71%; P > 0.05). Inpatient mortality did not change with or without CDE. Significant reductions were observed in the use of oral metronidazole (total: -32%; CDE specific: -70%) and vancomycin (total: -58%; CDE specific: -61%). There were no clusters detected pre-/post STA introduction. The need for isolation decreased from 748 to 181 patients post-intervention (-76%; P < 0.05). Annual cost savings were over $175, 000 due to decreases in laboratory testing followed by isolation, and antibiotic use. Conclusion: The switch to an STA from NAAT did not affect the diagnosis, treatment, or control of clinically relevant CDI in our institution. Benefits included avoidance of unnecessary antibiotic treatment, reduction in isolation, achieving publicly reported objectives, and costs savings. Selection of clinically relevant tests can help to improve hospitalization and treatment of patients and should be considered as part of diagnostic stewardship. Disclosures: All authors: No reported disclosures.